Analysis of The Effect of Appreciation From Leadership on Employee Motivation and Performance At PT Petirindo Jaya Abadi - Yosi Ragil Cahyono; Raniasari Bimanti Esthi (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
Staff encouragement andperformance serve a pivotal function in the success of one organization, especially in facing increasingly fierce business competition. Leadership appreciation is one of the key factors that can enhance work motivation and impact employee productivity and job satisfaction. This research seeks to examine how leadership impacts appreciation regarding employee motivation and work output at PT Petirindo Jaya Abadi. The study applies a numerical method through a survey technique through questionnaire distribution to employees. Data analysis is conducted using multiple linear regression to determine how much leadership appreciation influences staff drive and productivity. The findings suggest that leadership appreciation notably influences personnel motivation and performance. Employees who consistently receive appreciation demonstrate higher engagement, job contentment, and productivity. This paper also emphasizes the importance of implementing structured appreciation policies as a strategic tool to enhance work motivation and organizational effectiveness. Based on these findings, it is recommended that PT Petirindo Jaya Abadi strengthen leadership appreciation policies to create a more positive and performance-oriented work environment.